Effect of Using Pedada Fruit (Sonneratia caseolaris) Pectin with Glycerol as Edible Coating - Rahmah, Yunia Adilatur; Jariyah; Wicaksono, Luqman Agung (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Pectin, a natural polysaccharide, is widely utilized in the food industry, particularly as a base material for edible coatings due to its film-forming ability. Pedada fruit (Sonneratia caseolaris), a mangrove species rich in pectin, remains an underutilized resource despite its potential. This study aims to explore the application of pectin extracted from pedada fruit as a component of edible coatings, with the addition of glycerol as a plasticizer to enhance flexibility and reduce brittleness commonly observed in pure pectin films. A completely randomized design (CRD) with a factorial pattern was employed, consisting of two factors: pectin concentration (1%, 2%, and 3%) and glycerol concentration (1%, 2%, and 3%), each replicated three times. The data were analyzed using Analysis of Variance (ANOVA) at a 5% significance level, followed by Duncan's Multiple Range Test (DMRT) for treatments showing significant differences. Results indicated that increasing concentrations of pectin and glycerol significantly affected the water vapor transmission rate, film thickness, and viscosity of the edible coating. The optimal formulation was achieved with 3% pectin and 2% glycerol, yielding a water vapor transmission rate of 4.083 g/m²/day, film thickness of 0.128 mm, and viscosity of 1022.23 mPa·s. These findings highlight the potential of pedada-based pectin as an eco-friendly alternative for sustainable food packaging solutions. Contribution to Sustainable Development Goals (SDGs): SDG 12 – Responsible Consumption and Production: SDG 13 – Climate Action: SDG 14 – Life Below WaterSDG 15 – Life on Land: